2015
DOI: 10.1021/acssuschemeng.5b01344
|View full text |Cite
|
Sign up to set email alerts
|

Vanillin Production from Lignin and Its Use as a Renewable Chemical

Abstract: The use of vanillin as a building block for the chemical industry is discussed in this article. Vanillin is currently one of the only molecular phenolic compounds manufactured on an industrial scale from biomass. It has thus the potential to become a key-intermediate for the synthesis of bio-based polymers, for which aromatic monomers are needed to reach good thermo-mechanical properties. After a first part dedicated to the current sourcing of vanillin, this article focuses on the alkaline oxidation lignin-to-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
635
0
9

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 738 publications
(646 citation statements)
references
References 79 publications
2
635
0
9
Order By: Relevance
“…The depolymerised lignin products generated in the present study, i.e. guaiacol and vanillin, are known to have the potential of being key renewable aromatic building blocks for sustainable chemical industry [4,33].…”
Section: Supercritical Fluid Chromatography-mass Spectrometrymentioning
confidence: 99%
“…The depolymerised lignin products generated in the present study, i.e. guaiacol and vanillin, are known to have the potential of being key renewable aromatic building blocks for sustainable chemical industry [4,33].…”
Section: Supercritical Fluid Chromatography-mass Spectrometrymentioning
confidence: 99%
“…Mathias and Rodrigues [40] reported that lignin was dissolved by hydroxyl ions to form polyphenolate ions that further reacted with the oxidant via a free radical reaction to yield vanillin/syringaldehyde. Based on the available literature, it appears that higher pH > 10 is suitable for formation of aldehydes because lower pH accelerated subsequent oxidation of vanillin [52][53][54]. daSilva et al [55] observed a significant decrease in vanillin yields from lignin derived from Pinus sp and Indulin AT when pH of the reaction system was lowered from 14 to 10.…”
Section: Future Directionsmentioning
confidence: 99%
“…However, there are few methods for the valorization of lignin despite the extensive research ongoing in the area, and therefore most of the produced lignin is burned as fuel. Vanillin (4-hydroxy-3-methoxybenzaldehyde) is currently one of the few value-added chemicals commercially produced from lignin [2,3]. Vanillin along with its derivatives is widely used in food, perfume and pharmaceutical industries [4].…”
Section: Introductionmentioning
confidence: 99%
“…Vanillic acid, produced by selective oxidation of vanillin, has various chemical, biological and medicinal applications in addition to its use in food and fragrance industries [5][6][7]. The oxidation of lignin into vanillin can produce vanillic acid but is usually accompanied by undesired degradation processes [3,8]. To prepare vanillic acid, the selective oxidation of vanillin is therefore carried out using stoichiometric oxidants, such as chlorite and hexacyanoferrate(III) [9][10][11] or, in few cases, catalytic systems, namely hydrotalcites [5].…”
Section: Introductionmentioning
confidence: 99%